Scaling up co-cultivation fermentation of Lactococcus lactis ATCC 11454 and Lactobacillus rhamnosus ATCC 7469 with various feeding strategies - Abdul Halid, Nadra; Ibrahim, Mohamad Faizal; Haryani, Yuli; Mohd Zaini, Nurul Solehah; Hasan, Hanan (Hibiscus Publisher Enterprise, 2024)
This study aimed to analyse the effect of cocultivation between Lactococcus lactis ATCC 11454 with Lactobacillus rhamnosus ATCC 7469 through their growth profile, riboflavin and nisin production in 2.0 L stirred tank bioreactors. Batch fermentation was employed in the control (C) bioreactor, while fed-batch fermentation employed in bioreactor run (B1) and run 2 (B2), with different medium flow rates of 10 mL/min and 1.6 mL/min, respectively. Results showed that B1 was able to generate an increase of 33.5 % in riboflavin production and a 36% growth rate compared to C and B2. The application in the fermentation process resulted in a prolonged exponential phase, subsequently contributing to a longer metabolite production timeframe. The findings from this study provided an efficient prospect of LAB co-culture, potentially by extending riboflavin production time and increasing vitamin levels in fermented foods or facilitating the production of valuable metabolites.